The global loss of avian functional and phylogenetic diversity from anthropogenic extinctions - Matthews, TJ; Triantis, KA; Wayman, JP; Martin, TE; Hume, JP; Cardoso, P; Faurby, S; Whittaker, R (American Association for the Advancement of Science, 2024)
Humans have been driving a global erosion of species richness for millennia, but the consequences of past extinctions for other dimensions of biodiversity—functional and phylogenetic diversity—are poorly understood. In this work, we show that, since the Late Pleistocene, the extinction of 610 bird species has caused a disproportionate loss of the global avian functional space along with ~3 billion years of unique evolutionary history. For island endemics, proportional losses have been even greater. Projected future extinctions of more than 1000 species over the next two centuries will incur further substantial reductions in functional and phylogenetic diversity. These results highlight the severe consequences of the ongoing biodiversity crisis and the urgent need to identify the ecological functions being lost through extinction.